Grausamkeit Philosophische Positionen von der Antike bis in die Gegenwart. Mit einem einleitenden Essay und einem Überblick zur Diskussion im 20. Jahrhundert - Schotte, Dietrich (Wissenschaftliche Buchgesellschaft (wbg), 2023)
As a concept or problem of philosophy, "cruelty" seems to be something like a "white raven". For unlike most concepts and problems, philosophers from antiquity to modern times are surprisingly unanimous about what is meant by "cruelty" and how it is to be evaluated. "Cruelty" is excessive suffering and as such highly reprehensible. This unanimity is found not only in some examples of cruelty - torture, cruelty to animals, humiliation. The field of alternative, mostly strongly pejorative terms also changes only slightly. Since ancient times, it has been dominated by idioms that describe cruelty as "inhuman," usually as "bestial" or "brutalized." This also makes it clear: At least at first glance, philosophy seems to be in unusual harmony with our everyday beliefs. Nevertheless - or better: just because of that - it is worthwhile to have a look at the different philosophical classifications, discussions, considerations and analyses of cruelty. For behind the superficial unity, very different philosophical perspectives are hidden. Above all, one discovers divergent moral and ethical evaluations. For this reason, this anthology gathers the most important philosophical texts on the problem of cruelty from Aristotle to Nietzsche (in excerpts). These texts are complemented by a survey article that systematically organizes and summarizes the various discourses of the 20th century. Interested readers can thus gain an initial overview of the various positions and theses. At the same time, this anthology can also be used as a basis for school and university teaching.